Raloxifene but not alendronate can compensate the impaired osseointegration in osteoporotic rats - Faverani, Leonardo Perez [UNESP]; Polo, Tárik Ocon Braga [UNESP]; Ramalho-Ferreira, Gabriel [UNESP]; Momesso, Gustavo Antonio Correa [UNESP]; Hassumi, Jaqueline Suemi [UNESP]; Rossi, Ana Cláudia; Freire, Alexandre Rodrigues; Prado, Felippe Bevilacqua; Luvizuto, Eloá Rodrigues [UNESP]; Gruber, Reinhard; Okamoto, Roberta [UNESP] (Springer Nature, 2018)
Objectives: Alendronate and raloxifene, a bisphosphonate and a selective estrogen modulator, respectively, are established osteoporosis therapies. Current evidence suggests that simultaneous application of osteoporosis therapies modulates osseointegration. However, alendronate shows inconsistent findings and raloxifene has not been studied comprehensively. This study aimed to evaluate the bone dynamics and molecular and microstructural features at the peri-implant bone interface in osteoporotic rats. Materials and methods: Thirty female rats underwent ovariectomy and were fed a diet low in calcium and phosphate and treated with alendronate or raloxifene for 30 days or underwent fictional ovariectomy surgery (SHAM) prior to implant insertion in the tibia; osteoporosis therapies continued thereafter. After 42 days, peri-implant bone was evaluated by histometric and micro-CT analysis. Fluorochrome incorporation and gene expression was determined to evaluate bone turnover. Results: We report here that alendronate had no impact on bone-to-implant contacts and the mineral apposition rate. The RANKL/OPG ratio and local bone volume, however, were increased compared to the untreated osteoporotic rats. Even though signaling to bone resorption activity through RANKL production was observed in the alendronate group, the blockade of bone resorption activity that occurs in decorrence to alendronate activity took place and resulted in an increase in bone volume. Raloxifene significantly increased osseointegration in osteoporotic rats, as indicated by bone-to-implant contacts, mineral apposition, and local bone volume. Raloxifene, however, had no considerable impact on the RANKL/OPG ratio compared to untreated osteoporotic rats. As expected, the SH group showed higher bone-to-implant contacts and mineral apposition rates than the untreated osteoporotic rats. Conclusions: These findings suggest that raloxifene but not alendronate can compensate for the impaired osseointegration in osteoporotic rats. Clinical relevance: Regarding the superiority of raloxifene observed in the improvement of bone dynamics response, this statement suggests that raloxifene could be a good option for osteoporosis patients in oral rehabilitation procedures.
Keywords: Alendronate; Dental implants; Microscopy; Osteoporosis; Raloxifene